2021
DOI: 10.9734/jpri/2021/v33i51a33471
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of β-Carotene and Metformin on Antihyperglycemic and Antidyslipidemic Activities in Streptozotocin-Induced Diabetic Rats

Abstract: Purpose: Worldwide prevalence of diabetes mellitus (DM) has become an issue of great concern in current decades. To date, a large number of biological properties have been reported from carotenoids, particularly protective effects against cancer, cardiovascular diseases, and DM, including enhancement of insulin sensitivity.In this study, we aimed to evaluate the efficacy of β-carotene as an additive agent with metformin in ameliorating Type2 (T2)DM. Methods: In this experiment, fasting blood glucose leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To avoid the complication of metformin researcher hunt natural or herbal product or those substance which has ability to have antihyperglycemic and antihyperlipidemic activity. In this sense, the therapies based on an antioxidant β-carotene had the ability to improve the efficacy of glycemic control promoted by metformin to avoid the transition of insulin therapy is of great interest [30]. Also, it was found that the mono therapy of antioxidant; like as N-acetylcysteine, vitamin C, and α-lipoic acid had capability to reduced diabetes complications [31].…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the complication of metformin researcher hunt natural or herbal product or those substance which has ability to have antihyperglycemic and antihyperlipidemic activity. In this sense, the therapies based on an antioxidant β-carotene had the ability to improve the efficacy of glycemic control promoted by metformin to avoid the transition of insulin therapy is of great interest [30]. Also, it was found that the mono therapy of antioxidant; like as N-acetylcysteine, vitamin C, and α-lipoic acid had capability to reduced diabetes complications [31].…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are major food bioactive compounds in our diets, with antioxidant, anti-inflammatory and gut health functions [ 1 ]. The roles of carotenoids such as lycopene (LYC), astaxanthin and β-carotene in preventing chronic diseases and inhibiting cancer have been widely accepted [ 2 , 3 , 4 ]. Meanwhile, phytoene (PT) and phytofluene (PTF), known as the precursors in carotenoid synthesis ( Figure A1 ), and commonly called polyhydrogen lycopene, have attracted more and more attention [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%